Improved Nondestructive Disassembly Process using Augmented Reality and RFID Product/Part Tracking - Mircheski, Ile; Rizov, Tashko (TEM Journal, 2017)
The waste from electric and electronic equipment and discarded automobiles in the past grew rapidly and resulted with waste in billions of tones. The aim of this paper is to present an improved nondestructive disassembly process of electromechanical products using augmented reality based devices, such as glasses, tablets or mobile phones, and RFID technology for valuable product/part tracking. The proposed method includes tagging of components of interest in the product assembly by using a RFID tag. The valuable product is marked with specific ID number written in the RFID tag, in order to declare the product. The relevant data such as material and weight of components, guidelines for non-destructive disassembly for the valuable product and removing of component of interest will be obtained with the assistance of RFID tag and a centralized database. This modular system offers guidelines for the nondestructive disassembly process for obtaining valuable component of interest intended for easy repairs, remanufacture, reuse or recycling. The guidelines are in video presentation format using augmented reality for easy visualization of non-destructive disassembly process. The benefits of proposed modular system includes biggest percentage of reuse of the valuable components, easy maintaining, improved material recycling, environmental protection and greater total return form end of life products.
Keywords: nondestructive disassembly; reuse; augmented reality; RFID